IMPLEMENTASI SIKLUS ACE MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DALAM MENINGKATKAN KUALITAS PERKULIAHAN PENGEMBANGAN PROGRAM PEMBELAJARAN BIOLOGI - Any Fatmawati (Bioscientist : Jurnal Ilmiah Biologi, 2013)
The purpose of this research is to improve motivation, activity, learning achievement, and student's response to ACE cycle implementation (Activities, Class discussion, Exercises) through cooperative learning model of think pair share type. This Research Type is Classroom Action Research (PTK), conducted in semester Vc Biology Education Program Faculty of Mathematics and Natural Sciences Education IKIP Mataram Academic Year 2010/2011. The study was designed in three cycles, with activities in each cycle being planning, execution, observation and reflection. The data collected is data about motivation, activity, achievement learn, and student response semester Vc Biology Education Program. The result of data analysis shows that there is an increase on the average of motivation in cycle I of 33 with criteria classified enough to be average 42 with high criterion. For activity also experienced an increase that is on cycle I mean 12 with enough active criterion and in cycle II increased to 15 with active criterion. For student achievement in cycle I average 64 category is enough and in cycle II 71 with good category. For students' responses to the applied learning strategies the average class gets a positive assessment. Based on the results of the research can be concluded that the implementation of ACE cycle through cooperative learning model type think pair share can improve the quality of lectures of development of biology learning program (P3 Biology).